An ounce of prevention: quantifying the effects of non-lethal tools on wolf behavior - Much, Rebecca, author; Breck, Stewart, author; Lance, Nathan, author; Callahan, Peggy, author (Colorado State University. Libraries, 2017)
Human-carnivore conflict is presently on the rise as human populations continue to grow and carnivore conservation efforts gain precedence. The behaviors exhibited by carnivores that cause conflict are often learned; therefore, reducing learning potential though the use of prevention methods is important for coexistence. In this study we measured how prior experience (i.e., conditioning) influenced the motivation and persistence of captive wolves (Canis lupus) seeking a food reward by quantifying latency to first behavior and duration of behavior for two behavior groups: investigative and work behaviors. Latency to first behavior was faster in conditioned wolves for both investigative (11 times faster; P=0.011) and work (4 times faster; P=0.049) behaviors, indicating increased motivation to gain reward with prior experience. We found little difference in duration for both investigative (P=0.319) and work behaviors (P=0.702), indicating conditioned and non-conditioned wolves will spend similar amounts of time trying to obtain a reward once a behavior is learned. When wolves were unable to attain food rewards, we found that the duration of both investigative (P=0.0631) and work (P=0.0609) behavior declined over the course of three weeks for both non-conditioned (37.3% and 92.6% decline in investigative behaviors and work behaviors, respectively) and conditioned (59.5% and 88.2% decline in investigative behaviors and work behaviors, respectively) wolves, indicating decreased persistence with the application of a secure prevention measure. Overall, our results indicate that the use of measures that prevent animals from attaining anthropogenic food can effectively curb learning in carnivores and help reduce human-carnivore conflict.
202 - Rebecca Malaika Much
Quantifying the effects of non-lethal tools on wolf behavior
Keywords: human-wildlife conflict; learning; non-lethal; prevention; wolves; behavior; Canis lupus